A new species and new record of the genus Nannastacus (Crustacea: Cumacea: Nannastacidae) from Korea - Lee, Chang-Mok; Kim, Sung-Hyun; Kim, Young-Hyo (Zootaxa, 2017)
The new species, Nannastacus leeae sp. nov. and the newly recorded species, Nannastacus spinulosus Gamô, 1962 are described and illustrated. This new species resembles Nannastacus inconstans Hale, 1945, N. nyctagineus Gamô, 1962, and N. pectinatus Gamô, 1962 in having numerous minute granules on pereon and pleon. However, the new species is distinguished from its congeners by having several rows of large spatulate tubercles on carapace. The specimens of Nannastacus spinulosus herein studied coincided well with the descriptions given by Gamô, 1962. A key to the Korean species of Nannastacus is provided.